2003
DOI: 10.1210/en.2002-0181
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of Otoconin-22 Complementary Deoxyribonucleic Acid in the Bullfrog Endolymphatic Sac: Effect of Calcitonin on Otoconin-22 Messenger Ribonucleic Acid Levels

Abstract: Anuran amphibians have a special organ called the endolymphatic sac (ELS), containing many calcium carbonate crystals, which is believed to have a calcium storage function. The major protein of aragonitic otoconia, otoconin-22, which is considered to be involved in the formation of calcium carbonate crystals, has been purified from the saccule of the Xenopus inner ear. In this study, we cloned a cDNA encoding otoconin-22 from the cDNA library constructed for the paravertebral lime sac (PVLS) of the bullfrog, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Using a bullfrog PVLS cDNA library established in our previous study (Yaoi et al, 2003), we cloned cDNAs encoding the A-and Esubunits of V-ATPase. Partial cDNA fragments of bullfrog A-and Esubunits of V-ATPase were obtained by designing degenerate primers based on amino acid sequences from other species.…”
Section: Cloning Of Bullfrog A-and E-subunits Of V-atpasementioning
confidence: 99%
See 2 more Smart Citations
“…Using a bullfrog PVLS cDNA library established in our previous study (Yaoi et al, 2003), we cloned cDNAs encoding the A-and Esubunits of V-ATPase. Partial cDNA fragments of bullfrog A-and Esubunits of V-ATPase were obtained by designing degenerate primers based on amino acid sequences from other species.…”
Section: Cloning Of Bullfrog A-and E-subunits Of V-atpasementioning
confidence: 99%
“…We performed polymerase chain reaction (PCR) analyses using cDNA prepared from the bullfrog PVLS cDNA library in 25-μl volumes of Ex-taq buffer containing 0.2 mM each dNTP and 50 pmol of each of primers 1 and 2 with 0.5 U of Ex-taq polymerase (Takara, Kyoto, Japan), as described by Yaoi et al (2003). The PCR amplification procedure consisted of an initial denaturation step at 95°C for 5 min followed by denaturation (94°C, 90 sec), annealing (50°C, 90 sec), and extension (72°C, 150 sec) for 30 cycles in a thermal cycler (ASTEC, Fukuoka, Japan).…”
Section: Cloning Of Bullfrog A-and E-subunits Of V-atpasementioning
confidence: 99%
See 1 more Smart Citation
“…In the frog Rana catesbeiana, the levels of Otoconin22(Oc22) mRNA, the major core matrix protein of aragonitic otoconia (Pote and Ross, 1991;Pote et al, 1993), have been shown to be regulated by the activity of calcitonin (Yaoi et al, 2003), suggesting that, in some animals, otoconia serve as a rapidly ionizable store of Ca 2+ that can be (reversibly) demineralized and dispersed. In humans, bone serves as a readily ionizable and regulatable source of Ca 2+ , but as shown above, many of the systems for the formation and fate of otoconia are well conserved throughout vertebrates.…”
Section: Otoconial Calciummentioning
confidence: 99%
“…In a previous study, we found that otoconin-22 protein is present in the endolymphatic sac surrounding the pituitary gland and the paravertebral lime sac in the bullfrog (Yaoi et al 2001). Later, we cloned and sequenced a cDNA encoding bullfrog otoconin-22 and found that calcitonin regulates the expression of otoconin-22 mRNA in the endolymphatic sac, thereby stimulating the formation of calcium crystals in the lumen of the endolymphatic sac (Yaoi et al 2003b). Furthermore, we noted that the inner ear expressed otoconin-22 mRNA but not calcitonin receptor mRNA, although the receptor mRNA was expressed in the endolymphatic sac.…”
mentioning
confidence: 99%